Being Hakka Brides : A Case Study Of Bidayuh Women In A Hakka Village, Sarawak, Malaysia - Chai, Elena Gregoria Chin Fern (中央大学出版中心, 2013)
The mass arrival of Hakka to Sarawak was believed to have occurred during the period of gold rush during the middle of the eighteenth century from western Borneo also known as Kalimantan Indonesia (Chin, 1981). Immigrants from China, especially the Hakkas who came from an agricultural background, was helpful in ensuring their self sufficiency in food in addition to working in the gold mines where they also established the kongsi system, an organized Chinese social structure, to safeguard their economic interests and control over mining grounds. As mining activities intensified and the economy started to boom, kongsi began to thrive, both to repel against government action which tried to gain more control over the communities, and to garner more control over the trade of opium, guns and ammunition. In the failed 1857 rebellion against the ruling Brooke’s administration in Kuching, the Bau kongsi were defeated but gained increased diplomacy from the government in dealing with the ethnic groups. This eventually led to the establishments of homesteads of Hakka communities along the then Kuching-Serian by-pass.